Multiple regenerative techniques for class II furcation defect - Verma, Pushpendra Kumar; Srivastava, Ruchi; Gautam, Anju; Chaturvedi, T. P. (European Journal of General Dentistry, 2012)
Regeneration of the periodontium is a major goal in the treatment of teeth affected by periodontitis. Periodontal regeneration is quite challenging, especially when it is in the furcation area. There are several techniques used alone or in combination, considered to achieve periodontal regeneration, including bone grafts or substitutes, guided tissue regeneration, root surface modification, and biological mediators. Many factors may account for variability in the response to regenerative therapy in class II furcation. This case report describes the management of a buccal class II furcation defect, with the help of surgical intervention, including the guided tissue regeneration (GTR) membrane and bone graft materials. This combined treatment resulted in a healthy periodontium, with radiographic evidence of alveolar bone gain. This case report demonstrates that proper diagnosis, followed by removal of the etiological factors and utilizing combined treatment modalities, restored health and function of the tooth with severe attachment loss, at the 18-month follow-up.
Keywords: Class II furcation; furcation involvement; guided tissue regeneration; periodontal regeneration